Self-Reported Violence Experienced by Swiss Prehospital Emergency Care Providers - Simon Savoy; Pierre-Nicolas Carron; Nathalie Romain-Glassey; Nicolas Beysard (Emergency Medicine International)
Background. Workplace violence is a serious and increasing problem in health care. Nevertheless, only few studies were carried out concerning this topic and then mainly in English-speaking countries. The objectives were to describe the acts of violence experienced by prehospital emergency care providers (PECPs) in the western part of Switzerland between January and December 2016 and to assess the consequences for subsequent PECPs behaviors. Methods. An observational cross-sectional study, carried out using an online survey, has been sent to all 416 PECPs in the Canton of Vaud, in the western, French-speaking, part of Switzerland. The survey contained items of demographic data and items to assess the type and consequence of violence sustained. This was classified as five types: verbal assault, intimidation, physical assault, sexual harassment, and sexual assault. Results. 273 (65.6%) PECPs participated in the survey. During 2016, workplace violence was reported by 229 survey participants (83.9%). Most declared to be the victim of such violence between one and three times during the year. In all cases of violence described, the patient and/or a relative initiated aggressive behavior in 96% of cases. Verbal assaults were the most common (99.2% of all acts), followed by intimidation (72.8%), physical assault (69.6%), and sexual harassment (16.3%). Concerning physical assault, PECPs were predominantly victims of spitting and/or jostling (50%). After a violent event, in 50% of cases, the PECPs modified their behavior owing to the experience of workplace violence; 82% now wear protective vests, and 16% carry weapons for self-defense, such as pepper sprays. Seventy-five percent changed their intervention strategies, acting more carefully and using verbal de-escalation techniques or physical restraints for violent patients. Conclusions. Workplace violence is frequent and has significant consequences for PECPs. In order to increase their own security, they increased their protection. These results illustrate their feelings of insecurity, which may have deleterious effects on work satisfaction and motivation. Trial Registration. Our article does not report the results of a health care intervention on human participants.